2020
DOI: 10.3139/146.111914
|View full text |Cite
|
Sign up to set email alerts
|

On the evaluation of the constrained studded pressing method for producing nanocrystalline copper sheets

Abstract: In this study, the experimental setup of a constrainedstudded- pressing method (CSP) as a severe plastic deformation process was investigated to produce nano-crystalline copper sheets. The sheets were CSPed up to 35 passes. The crystallite size and the dislocation density of CSPed samples were calculated by X-ray-diffraction pattern analysis. Also, tensile tests were used to investigate the mechanical properties of the CSPed samples. The results revealed that increasing the number of CSP passes augmented the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Regarding its cause, it is accepted that the plastic deformation can be related to the evolution of dislocations and the interaction of dislocations. There are several models suggested which deal with generation and annihilation of dislocations in plastic deformation of polycrystalline metals [24,25]. Also, the relationship between the microscopic plastic deformation mechanism and the notion of dislocation is generally accepted.…”
Section: Microstructure Observationsmentioning
confidence: 99%
“…Regarding its cause, it is accepted that the plastic deformation can be related to the evolution of dislocations and the interaction of dislocations. There are several models suggested which deal with generation and annihilation of dislocations in plastic deformation of polycrystalline metals [24,25]. Also, the relationship between the microscopic plastic deformation mechanism and the notion of dislocation is generally accepted.…”
Section: Microstructure Observationsmentioning
confidence: 99%
“…The presence of sharp edges in the CSP dies was the main cause of stress concentration and local strain in sheets under plastic deformation [14]. So, the amount of plastic deformation of the sheet is limited in the CSP method.…”
Section: Illustration Of the Proposed Die Designmentioning
confidence: 99%
“…Regarding the cause, it is accepted that plastic deformation can be related to the evolution of dislocations and the interaction of dislocations. There are several models suggested that deal with generation and annihilation of dislocations in plastic deformation of polycrystalline metals [14,25]. Moreover, the relationship between the microscopic plastic deformation mechanism and the notion of dislocation is generally accepted.…”
Section: Tensile Propertiesmentioning
confidence: 99%
See 1 more Smart Citation